Rice research, technological progress, and impacts on the poor: the Bangladesh case (summary report) - Hossain, Mahabub; Lewis, David; Bose, Manik L.; Chowdhury, Alamgir (International Food Policy Research Institute, 2003)
This case study builds on an ongoing large-scale quantitative research project undertaken by BIDS/IRRI since 1987 originally in 64 unions from 57 districts of the country. It adds a qualitative research component to examine the impact of modern rice varieties (MVs) on livelihoods in a structured sample of eight of these villages across a range of favorable and unfavorable contexts..... The quantitative research shows that for households with access to land there have been direct adoption impacts in the form of increased yields and higher profits. However, since rice now only represents around 20 percent of most households’ overall income, nonagricultural income is found to have gained dramatically in importance for rural households. While the profitability has declined over time, rice contributes to improved food security and provides a “springboard” for both rich and poor farm households moving into nonfarm income generation and employment... The qualitative research component generally confirmed these general findings, highlighting other factors such as the improved status associated with fixed-rent tenancy and “contract” labor arrangements. The qualitative research also shows negative adoption impacts such as shrinking common property resources (wild fish, vegetables, etc., and declining soil fertility, both of which may increase the long-term vulnerability of the poor. It also throws light on the processes of technology dissemination.... It was found that the linking of qualitative and quantitative research methodologies was useful in (a) generating complementary data of different kinds on similar issues and (b) generating new data missed within a purely quantitative approach. The sustainable livelihoods framework was a useful, flexible tool for structuring the qualitative data collection and analysis. However, the research study as a whole was limited by the fact that the qualitative component was “bolted onto” a quantitative study already underway. Therefore the framework, and the various data collection methodologies, were not systematically integrated across both components of the study. In conclusion, future agricultural research on rice may need to further address the question of MV adoption potential on risk-prone lands, the relevance of existing technology dissemination systems, the relationship between MV adoption and crop diversification, and the challenges of more sustainable crop management techniques. -- Authors' Abstract